2002
DOI: 10.1530/rep.0.1240683
|View full text |Cite
|
Sign up to set email alerts
|

Developmental competence and oxidative state of mouse zygotes heat-stressed maternally or in vitro

Abstract: Mammalian preimplantation embryos are sensitive to maternal and direct heat stress. However, the mechanisms by which heat stress affects early embryonic development in vivo or in vitro are unknown. This study examined whether heat-stress-induced loss of developmental competence in mouse embryos was mediated by physiological changes in the maternal environment or by high temperatures alone. After fertilization, zygotes at the same stage were heat-stressed at 39.5 degrees C for 12 h either maternally (measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(56 citation statements)
references
References 7 publications
2
53
0
1
Order By: Relevance
“…The embryonic death from maternal hyperthermia was partially ascribed to the high susceptibility of embryos to oxidative stress in bovine [3] and porcine [4] species. The excessive ROS from oxidative stress induced the damages of lipid, protein and DNA and then arrested development of embryos [21, 22, 23]. However, lipid peroxidation was not observed in the livers of maternal heat-stressed embryos based on MDA content.…”
Section: Discussionmentioning
confidence: 99%
“…The embryonic death from maternal hyperthermia was partially ascribed to the high susceptibility of embryos to oxidative stress in bovine [3] and porcine [4] species. The excessive ROS from oxidative stress induced the damages of lipid, protein and DNA and then arrested development of embryos [21, 22, 23]. However, lipid peroxidation was not observed in the livers of maternal heat-stressed embryos based on MDA content.…”
Section: Discussionmentioning
confidence: 99%
“…SE (Bruce and Baudry 1995; Gluck et al 2000; Liang et al 2000; Patel et al 2001; Tejada et al 2007; Jarrett et al 2008a; Waldbaum et al 2010). In addition to SE, other injuries that are capable of leading to chronic acquired epilepsies such as hypoxic-ischemic insults, traumatic brain injury, viral infection and hyperthermia can individually produce mitochondrial dysfunction and oxidative stress (Ozawa et al 2002; Gil et al 2003; Xu et al 2004; Chang et al 2007; Bhargava et al 2010; Mustafa et al 2010; Schwarzbold et al 2010). This suggests that mitochondrial dysfunction may be at least one final common factor that contributes to epileptogenesis.…”
Section: Mitochondrial Dysfunction and Oxidative Stress: Acute Conseqmentioning
confidence: 99%
“…Studies have shown that lactating sows exposed to high temperatures had reduced feed intake and milk production [26,27]. Hyperthermia from heat stress stimulates reactive oxygen species production causing oxidative damages [28]. A study was recently conducted to investigate the effects of hyperthermal conditions on oxidative status, and reproductive performance of sows during gestation and lactation [19].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased antioxidant capacity during late gestation and lactation can increase oxidative damage by increased production of free radicals when an animal is under high ambient temperature environment [28,29]. This indicates that oxidative stress is one of major stress responses caused by heat stress.…”
Section: Introductionmentioning
confidence: 99%